ANALISIS PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM PENETAPAN HARGA POKOK PRODUKSI (STUDI KASUS PADA TOKO ROTI KAHANG JAYA LILIBA KUPANG) - Dewi, Chelssy Angeleana; Oematan, Herly; Dethan, Minarni A. (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2024)
The study entitled Analysis of Cost of Production Using Activity Based Costing System (Case Study at Kahang Jaya Liliba Bakery, Kupang City), purposes to resolve and analyze the estimation of the production’s price applying the Activity Based Costing System. Techniques to gather the data used in this study such as documentation, interviews, and observations at the Kahang Jaya Liliba Bakery, Kupang City. The goal of the analysis is the cost of making bread, including factory overhead costs, raw material prices, and direct labor prices at Kahang Jaya Liliba Bakery, Kupang City in 2023. The result showed that Sweet Pork Bread and Spicy Pork Bread experienced undercosting (lower cost) in the Convesional Method other than the Activity Based Costing Method. For Sweet Buns and White Bread experienced overcosting (higher costs) in the Convetional Method than the Activity Based Costing System.